Behavioral biases, information acquisition and decisions of individual investors in Pakistan stock exchange - Naveed, Farrukh (2022)
In terms of returns, equity securities generally outperform other financial assets. However, contemporary research witnessed that individual investors remained less fortunate in getting benefits from stock market owing to their irrational choices as their investment decisions are motivated by behavioral factors. Extant literature confirmed that behavioral factors predict irrational trading behavior of individual investors, however, sufficient understanding is not yet reached to reduce the biased behavior of investors. Therefore, this study was conducted to investigate the impact of behavioural biases (overconfidence bias, self-attribution, availability bias, anchoring bias) and stress on the decision making of individual investors of Pakistan Stock Exchange (PSX). Besides, it was also intended to document the potential of information acquisition in reducing the biased behavior of individual investors. Using cluster sampling technique, questionnaire based quantitative data was collected from individual investors trading in PSX. Partial Least Squares Structural Equation Modelling (PLS-SEM) was applied on 390 useable questionnaires for data analysis. Result showed that overconfidence bias, availability bias, anchoring bias and stress are significantly associated with irrational investment decisions of individual investors. Furthermore, results revealed that self-attribution is not significant predictor of irrational decisions of investors. The result also revealed that moderating effect of information acquisition on the relationship of self-attribution and availability bias with investor decisions is not statistically significant. However, the information acquisition significantly moderates the relationship of overconfidence bias, anchoring bias and stress with individual investor decisions. Therefore, it can be asserted that acquisition of investment related information is essential for rational investment choices and earning superior returns from stock market. Furthermore, this study is beneficial for policymakers, as individual investors' financial well-being is critical to a country's long-term economic success.